A rare case of Brooke-Spiegler syndrome: integrated surgical treatment of multiple giant eccrine spiradenomas of the head and neck in a young girl. (2018) - Portincasa, A.; Cecchino, L.; Trecca, E.M.C.; Lembo, F.; Annacontini, L.; Ciancio, F.; Corsi, F.; Cassano, M.; Parisi, D.
Highlights: The authors present a rare case of multiple giant eccrine spiradenomas of the head and neck. A young girl presented with multiple swellings over the head and neck. The patient had a psychological trauma with a negative impact on her social life. There is need to establish a surgical protocol for the treatment of adnexal tumors. Our integrated surgical approach showed excellent aesthetic and functional results. Abstract: Introduction: The authors present a "four-step" integrated surgical protocol to treat a rare case of multiple giant eccrine spiradenoma (ES) of the head and neck in a young patient. Presentation of case: An 18-year-old female patient presented with multiple swellings in the head and neck regions. The patient had a severe psychological trauma with a negative impact on her social life. Physical examination revealed multiple papulo-nodular swellings measuring between 5 cm × 8 cm and up to 10 cm × 20 cm in size with cerebriform aspect and soft consistency. Major lesions were located in the scalp, frontal area, neck, occipitotemporal, and retroauricular regions. Tissue biopsy found a benign composite adnexal neoplasm consisted in ES, trichoepithelioma, and cylindroma, a typical feature of Brooke-Spiegler Syndrome. A staged excision was planned, and available reconstructive options were considered. Scalp reconstruction included tissue expansions, advancement flaps, skin grafts, and dermal regeneration template (Integra ® ). All treatments were successful, and no recurrence was observed. The patient returned to a normal social life, and a radical excision with satisfying aesthetic results was achieved. Discussion: Although adnexal tumors are benign in most of the cases, these lesions are prone to arise in the craniofacial region, thereby causing aesthetic discomfort associated with pain, hemorrhage, and infection to the patient every day. Furthermore, there is a potential risk of malignant transformation. These concerns demonstrate the need to establish a surgical protocol for the treatment of adnexal tumors. Conclusions: Our integrated surgical approach showed excellent aesthetic and functional results with benefits to the patient's life and complete oncological excision.